The human placenta - Jauniaux, Eric (Henry Stewart Talks, 2024)
Development and role of the human placenta, Early placentation, First trimester placenta, The definitive placenta, Utero-placental and intra-placental circulation, The extra villous trophoblast, Oxygen control and placental development, Formation of the placental membranes, The role of the placenta in fetal nutrition, placental related disorders of human pregnancy